Genetic variation in PNPLA3 (adiponutrin) confers sensitivity to weight loss-induced decrease in liver fat in humans - Sevastianova, Ksenia; Kotronen, Anna; Gastaldelli, Amalia; Perttilä, Julia; Hakkarainen, Antti; Lundbom, Jesper; Suojanen, Laura; Orho-Melander, Marju; Lundbom, Nina; Ferrannini, Eleuterio; Rissanen, Aila; Olkkonen, Vesa M; et al. (The American journal of clinical nutrition, 2011)
BACKGROUND: The rs738409 C[rightward arrow]G single nucleotide polymorphism in the patatin-like phospholipase domain-containing 3 (PNPLA3; adiponutrin) leads to a missense mutation (I148M), which is associated with increased liver fat but not insulin resistance. The I148M mutation impedes triglyceride hydrolysis in vitro, and its carriers have an increased risk of developing severe liver disease. OBJECTIVE: We explored whether the rs738409 PNPLA3 G allele influences the ability of weight loss to decrease liver fat or change insulin sensitivity. DESIGN: We recruited 8 subjects who were homozygous for the rs738409 PNPLA3 G allele (PNPLA3-148MM) and 10 who were homozygous for the rs738409 PNPLA3 C allele (PNPLA3-148II). To allow comparison of changes in liver fat, the groups were matched with respect to baseline age, sex, body mass index, and liver fat. The subjects were placed on a hypocaloric low-carbohydrate diet for 6 d. Liver fat content (proton magnetic resonance spectroscopy), whole-body insulin sensitivity of glucose metabolism (euglycemic clamp technique), and lipolysis ([²H₅]glycerol infusion) were measured before and after the diet. RESULTS: At baseline, fasting serum insulin and C-peptide concentrations were significantly lower in the PNPLA3-148MM group than in the PNPLA3-148II group, as predicted by study design. Weight loss was not significantly different between groups (PNPLA3-148MM: -3.1 ± 0.5 kg; PNPLA3-148II: -3.1 ± 0.4 kg). Liver fat decreased by 45% in the PNPLA3-148MM group (P < 0.001) and by 18% in the PNPLA3-148II group (P < 0.01). CONCLUSION: Weight loss is effective in decreasing liver fat in subjects who are homozygous for the rs738409 PNPLA3 G or C allele. This trial was registered at www.hus.fi as 233775.